2018
DOI: 10.1590/18069657rbcs20170305
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Responses of Soybean to Different Potassium Fertilization Management Practices in Years with High and Low Precipitation

Abstract: Brazilian soybean producers commonly apply maintenance potassium (K) fertilization during cultivation to restore the K taken up by plants; however, this measure can modify the morphophysiological plant characteristics, since the functions of K are closely related with plant growth and development. This study assessed the morphological changes in soybean plants in response to K rates, sowing fertilization, and the application periods of K fertilization in a Latossolo Vermelho eutroférrico (Oxisol) under a no-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Batistella Filho (2012) applying K rates cited that water unbalance could negatively influence, especially when it occurs near the harvest. In the 2017/18 growing season there were no differences for the seed mass, and the average obtained was 140.6 g. One of the possible causes may have been the lower water availability in this growing season, since some authors indicated that the plant responses to available K are clearer in adverse conditions mainly in lower water availability (Sangakkara et al, 2001;Wang et al, 2013;Zörb et al, 2014;Esper Neto et al, 2018).…”
Section: Electrical Conductivity Potassium Leaching and Potassium Sementioning
confidence: 94%
See 1 more Smart Citation
“…Batistella Filho (2012) applying K rates cited that water unbalance could negatively influence, especially when it occurs near the harvest. In the 2017/18 growing season there were no differences for the seed mass, and the average obtained was 140.6 g. One of the possible causes may have been the lower water availability in this growing season, since some authors indicated that the plant responses to available K are clearer in adverse conditions mainly in lower water availability (Sangakkara et al, 2001;Wang et al, 2013;Zörb et al, 2014;Esper Neto et al, 2018).…”
Section: Electrical Conductivity Potassium Leaching and Potassium Sementioning
confidence: 94%
“…and Diaporthe phaseolorum f. sp. meridionalis (Basseto et al, 2007), low water availability (Esper Neto et al, 2018) and lodging.…”
Section: Introductionmentioning
confidence: 99%
“…Among the main abiotic factors that seriously compromise grain yield, nutritional management stands out due to the inherent low fertility of tropical soils, their high degree of weathering, and the frequent use of fertilizers at a low concentration. These challenges make nutritional management a crucial aspect of maintaining productivity [9][10][11]. The experimental site is cultivated under a no-tillage planting system, with a soybean/corn or soybean/wheat succession, with mechanized planting, and without an irrigation system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the low fertility of Cerrado soils is the main cause of the gap between the low crop-grain yield and their productive potential, and the low K availability represents one of the most limiting factors for soybean development and productivity [6][7][8]. This low availability of K is even more limiting in sandy, sandy loam, and sandy clay loam soils, which are predominant in the Cerrado region, due to the high susceptibility of these soils to K losses by leaching [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the root system to acquire large amounts of K from the soil and translocate this nutrient to the shoots of plants plays a key role in improving the K-use efficiency of soybean genotypes [19]. Therefore, the use of soybean genotypes with a vigorous root system capable of extracting large amounts of exchangeable K from the soil, or roots with a greater capacity to solubilize non-exchangeable K from the soil through the exudation of organic acids, is fundamental for the sustainability of Brazilian soybean production systems [6,13,20]. This fact has been even more relevant in recent years, because farmers use new soybean genotypes with greater productive potential each growing season, increasing the requirement and demand for soil K in Brazilian soybean fields [13].…”
Section: Introductionmentioning
confidence: 99%